Child maltreatment and mental health problems in adulthood: birth cohort study. (28th September 2018) - Kisely, Steve; Abajobir, Amanuel Alemu; Mills, Ryan; Strathearn, Lane; Clavarino, Alexandra; Najman, Jake Moses
Abstract : Background: Retrospective studies have shown a high association between child abuse and subsequent psychiatric morbidity. Prospective studies are rarer. Aims: To examine, using a prospective record-linkage analysis, whether substantiated child maltreatment is associated with adverse psychological outcomes in early adulthood. Method: The participants were 3778 mother and child pairs enrolled in a population-based birth cohort study in Brisbane, Australia. Exposure to suspected child maltreatment was measured by linkage with state child protection agency data. The primary outcomes were the internalising and externalising scales of the Youth Self-Report and the Centre for Epidemiological Studies-Depression scales (CES-D) at approximately 21 years of age. A subset completed the Composite International Diagnostic Interview-Auto version (CIDI-Auto). Results: In total, 171 (4.5%) participants had a history of substantiated child maltreatment, most commonly emotional abuse ( n = 91), followed by physical abuse ( n = 78), neglect ( n = 73) and sexual abuse ( n = 54). After adjustment for potential confounders, depressive symptoms on the CES-D, as well as internalising and externalising behaviours were strongly associated with substantiated abuse in all forms, except sexual abuse. The results for the subset of the sample who completed the CIDI-Auto were less clear. Anxiety, especially post-traumatic stress disorder, showed the strongest association whereas the findings for depressive disorder were equivocal. However, across all diagnostic categories, emotional abuse and neglect, as well as multiple forms of abuse, showed a consistent association. Conclusions: Child maltreatment, particularly neglect and emotional abuse, has serious adverse effects on early adult mental health. These two warrant the attention given to other forms of child maltreatment. Children experiencing more than one type of maltreatment are at particular risk. Declaration of interest: None.